MyMukim2Cloud collaborative system: A mosque collaborative network for enhancing and serving the society needs in Malaysia - Saleh, Burhan; Ma-Key, Nalinee; Ahmad Dahlan, Abdul Rahman; Ahmad H.Osman, Rahmah (2013)
This conceptual paper seeks to put forth a novel vision, namely the combined deployment of the Quadruple Helix Model (QHM) collaboration mooted by Agensi Inovasi Malaysia, a Whole-of-Government (WoG) concept of ICT implementation across the Malaysian government agencies mooted by Malaysia Administrative and Modernization Planning Unit (MAMPU) and the Network of Mosques (NoM). This will be accomplished through leveraging the advances in cloud computing and mobile applications that could be used to set up what is proposed to be called the Collaborative MyMukim2Cloud System. The QHM actors, namely the Government, Academia, Industry and Citizen need to collaborate and share resources in nurturing and addressing the needs of less privileged and less fortunate people holistically, rather than the current practice which is executed in silos, isolation or independently. This proposed collaborative inter-organizational system is to enable a WoG and consolidated approach for government agencies, NGOs, the private sector and individuals in building up a single and trusted national database based on three (3) focus groups of people proposed in this paper, namely the Orphanage, the Poor and the Disabled. This database, proposed to be co-owned and managed by government agencies such as Department of Social Welfare (DSW) and Department of Islamic Development Malaysia (JAKIM), can be used and updated by all other authorized and relevant organizations and individuals in making a consolidated contribution in nurturing and developing these groups. Thus, this System shall eliminate unnecessary and duplication in data, efforts and investments made by the various organizations. The expected outcome of MyMukim2Cloud System will be an enhanced quality of life for the proposed focus groups through the execution of social entrepreneurship concept in healthcare, education and financial activities provided by the QHM collaborators.